Using specific purpose grants to achieve developmental goals: some practical considerations. Issue 6 (18th August 2022) - Harris, Jamelia
ABSTRACT: This practice note reviews the theory of conditional grants and their use in five countries (Rwanda, Kenya, South Africa, Uganda, and India). The note makes the case for conditional specific purpose grants based on theory and then puts forward five practical suggestions that can guide developing countries in designing specific purpose grants. These include setting clear conditions, establishing robust monitoring systems, developing sub-national capacity, being cognisant of sub-national autonomy, and simplifying the transfer system as best possible.